2021
DOI: 10.1002/lt.26366
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Adverse Effects of the 2‐Dose BNT162b2 Messenger RNA Vaccine Among Liver Transplantation Recipients

Abstract: The BNT162b2 messenger RNA (mRNA) vaccine against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been shown to be safe and effective in immunocompetent patients. The safety and efficacy of this vaccine in liver transplantation (LT) recipients is still under evaluation. The objective of this study was to assess the safety and efficacy of the BNT162b2 vaccine among transplant recipients. The immune responses of 76 LT recipients receiving 2 doses of the vaccine were compared with those of 174 ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 26 publications
3
64
1
4
Order By: Relevance
“…Adverse effects (mostly mild) were reported by 50% of the patients after the second dose of BNT162b2 mRNA vaccine 10 . Following the third dose, adverse effects were mild and reported by 37% of patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Adverse effects (mostly mild) were reported by 50% of the patients after the second dose of BNT162b2 mRNA vaccine 10 . Following the third dose, adverse effects were mild and reported by 37% of patients.…”
Section: Resultsmentioning
confidence: 99%
“…The reduced immune response was observed more in patients who received combined immunosuppression treatments (combination of calcineurin inhibitor (CNI) with mycophenolate mofetil (MMF), or sirolimus, or everolimus, and/or low-dose steroids) and patients with renal impairment 4 , 5 , 6 , 7 . We have reported a 72% positive immune response rate among 76 LT recipients after the second dose of the BNT162b2 mRNA vaccine 10 . Kamar et al reported improved immune response after the third BNT162b2 mRNA dose, administered to SOT recipients (78 kidney-transplant recipients, 12 LT recipients, eight lung-trans- plant or heart-transplant recipients, and three pancreas transplant recipients) 61 days after the second dose 11 .…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…2 However, we have observed suboptimal vaccine responses in some of our gastroenterology patient cohorts. Patients with inflammatory bowel disease (IBD) treated with infliximab were demonstrated to have attenuated antibody responses, 3 as did patients post liver transplantation 4 and those with chronic liver disease. 5 Subsequently, the British Society of Gastroenterology (BSG) has recommended and advocated for booster dosing in these cohorts.…”
mentioning
confidence: 99%